Multiple mutations in polyketide synthase led to disruption of Psittacofulvin production across diverse parrot species - Shatadru Ghosh Roy; Jindřich Brejcha; Petr Maršík; Anna Bakhrat; Moty Abdu; Roberto Arbore; Pedro Miguel Araújo; Sandra Afonso; Miguel Carneiro; Iris Grossman-Haham; Uri Abdu (Communications Biology)
Abstract Polyketide synthases (PKSs) are crucial multidomain enzymes in diverse natural product biosynthesis. Parrots use a type I PKS to produce a unique pigment called psittacofulvin in their feathers. In domesticated budgerigars and lovebirds, the same amino acid substitution (R644W) within malonyl/acetyltransferase (MAT) domain of this enzyme has been shown to cause the blue phenotype with no psittacofulvin pigmentation, proposing a strong evolutionary constraint on the mechanism. Here, we identified seven previously unreported variants in PKS associated with defective psittacofulvin production in four diverse species, including three nonsense mutations. Intriguingly, three of the remaining nonsynonymous substitutions reside within the ketoacyl synthase (KS) domain, whereas one at MAT domain. The heterologous expression of these PKS variants in yeast confirmed complete or partial loss of psittacofulvin production. These findings establish PKS as a functionally conserved key-enzyme determining psittacofulvin-based hues among diverse parrots, highlighting multiple conserved domains essential for the PKS function.